Self-assembly of nickel phosphate-based nanotubes into two-dimensional crumpled sheet-like architectures for high-performance asymmetric supercapacitors. (January 2020) - Wulan Septiani, Ni Luh; Kaneti, Yusuf Valentino; Fathoni, Kresna Bondan; Wang, Jie; Ide, Yusuke; Yuliarto, Brian; Nugraha; Dipojono, Hermawan Kresno; Nanjundan, Ashok Kumar; Golberg, Dmitri; Bando, Yoshio; Yamauchi, Yusuke
Abstract: This work demonstrates the successful self-assembly of amorphous nickel phosphate-based nanotubes into two-dimensional (2D) crumpled sheet-like architectures for the first time by employing nickel glycerate particles as sacrificial templates through a two-step phosphoric acid-assisted solvothermal method. A "self-deconstruction-self-weaving" mechanism is believed to be responsible for the formation of such nanotube-assembled crumpled sheet-like architectures from the nickel glycerate template. The asymmetric supercapacitor (ASC) device assembled using nanotube-assembled amorphous 2D nickel phosphate (NiHPi-500) as the positive electrode and activated carbon (AC) as the negative electrode exhibits high energy densities of 50 W h kg -1, 40 W h kg -1, and 32 W h kg -1 at power densities of 362 W kg -1, 1443 W kg -1, and 2838 W kg -1, respectively. Furthermore, this ASC device can retain an impressive energy density of 18 W h kg -1 at high power density of 7242 W kg -1 . In addition, the NiHPi-500//AC ASC also displays good long-term stability with a high capacitance retention of 100% after 5000 cycles at a high current density of 10 A g -1 . The excellent electrochemical performance is attributed to the unique nanotube-assembled 2D architectures, the good interconnectivity between the nanotubes, and the large surface area arising from such structures which can provide many active sites for the redox reactions and facility effective transport and diffusion of the electrolyte ions, leading to more efficient utilization of the active material. These results indicate the promising potential of nanotube-assembled 2D nickel phosphate nanoarchitectures for supercapacitor applications. Graphical abstract: This work reports the self-assembly of amorphous nickel phosphate-based nanotubes into two-dimensional crumpled sheet-like nanoarchitectures for high-performance asymmetric supercapacitors with a maximum energy density of 50.0 Wh kg -1 at a power density of 362 W kg -1 . Image 1 Highlights: The self-assembly of nickel phosphate nanotubes into 2D architecture is achieved. The nanotube-assembled 2D structure is obtained using nickel glycerate template. The nanotube-woven 2D structure is formed via self-deconstruction-self-weaving. The NiHPi-500//AC ASC shows high energy density and excellent long-term stability.